ANALISIS PENGARUH PERAN SUPERVISOR DAN PELATIHAN TERHADAP KINERJA TENAGA PENJUALAN PT. NASMOCO GOMBEL SEMARANG - Ika Putri Utami; Agus Hermani; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2014)
the most important elements in an organization is the human being. So that organization needs employees who are skilled and improve the performance continual. This research aims to describe  the influence of the role of supervisor and training on the salesperson performance of PT.Nasmoco gombel. Collection data methods was  using the study of library research,questionnaire and interviews. The sample method is  census of the entire population of 39 respondents were sampled. Measurement was using Likert Scale.Analysis technique was using qualitative and quantitative method. the results it can be concluded partially variable training have more influence  than role of supervisor. It can be proved by regression test that the role of supervisor has positive influence on salespeople performance  of 38,1%,and  the variable training has positive influence on salesperson performance of 63,6%. Simultaneously variables role of supervisors and training has a positive influence on the salesperson performance of 65.9%.